LIBRARIANS' ROLE IN PROCESSING DIGITAL COLLECTIONS FOR THE BENEFIT OF LIBRARY AND ARCHIVES IN SOUTH SULAWESI PROVINCE - Nadzar Samsudin; Iskandar; Muh. Quraisy Mathar; Noerjihad Saleh; Andi Ibrahim (Jurnal Diskursus Islam, 2022)
The goal of this study was to ascertain the librarian's role in processing digital collections and to ascertain the procedure by which digital collections were processed. The author employed descriptive research with management and pedagogical perspective in this study. Then, primary and secondary data were used in this study. Interviews and documentation served as guidance for the research instrument. Data collection techniques included observing, interviewing, and documenting. Then there were procedures for data analysis such as data reduction, data display, and conclusion drafting. The study's findings indicated that librarians played an important role in processing digital collections at the Library and Archives Service of South Sulawesi Province, including participation in librarian training activities, digital collection processing activities, and digital collection promotion activities. The Library and Archives Service of South Sulawesi Province were in the process of processing digital materials, specifically scanning, editing, and publishing. The processing of digital collections could be adapted to technological advancements to make them more effective and efficient.